PENINGKATAN MUTU CALON GURU PAIMELALUI PENGEMBANGAN SOFT SKILL DI PERGURUAN TINGGI AGAMA ISLAM - Khoirunnisa, Khoirunnisa (IAIN Padangsidimpuan, 2019)
The purpose of this research is to know thestrategy of improving the quality of Islamic Religious Educationteacher candidate in Universitas Muhammadiyah Tapanuli Selatan (UMTS). The research method used isqualitative research method. This research used observation,interview and d ocumentation for the data collection tools andanalyzed by using interactive analysis. The result of the researchshows that the strategy of improving the quality of Islamic ReligiousEducation teachers in UMTS is divided into several strengthenings,namely strengthening of Islam, strengthening the field of PAI study, aswell as the strengthening of foreign languages (English and Arabic),both through intra-curricular or co-curricular. Changes in the worldof work in educational institutions should be prepared by universitiespreparing educators and other education personnel so that a studentmust be trained and trained to have the competencies described inthree levels; perform, manage, and evaluate the process.